2014
DOI: 10.1002/pola.27131
|View full text |Cite
|
Sign up to set email alerts
|

Thiol‐functionalized 1,3‐benzoxazine: Preparation and its use as a precursor for highly polymerizable benzoxazine monomers bearing sulfide moiety

Abstract: We describe a new strategy for preparation of benzoxazine monomers based on in situ preparation of a thiol‐functionalized benzoxazine and successive chemical modification of the thiol moiety. The thiol‐functionalized benzoxazine can be prepared from its precursor bearing two benzoxazine moieties linked by disulfide bond. Reductive cleavage of the disulfide bond of the precursor with using triphenylphosphine as a reducing agent allows successful preparation of the thiol‐functionalized benzoxazine. By performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…As it has been reported that the polymerization does not alter the benzoxazine ring group, the obtained PMMA chains still possess chemically active benzoxazine groups observed with 1 H NMR analysis (see supporting materials). As a result, further reaction and modification on the benzoxazine‐possessing PMMA could be performed such as self‐polymerization and thiol‐addition reaction …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As it has been reported that the polymerization does not alter the benzoxazine ring group, the obtained PMMA chains still possess chemically active benzoxazine groups observed with 1 H NMR analysis (see supporting materials). As a result, further reaction and modification on the benzoxazine‐possessing PMMA could be performed such as self‐polymerization and thiol‐addition reaction …”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] The sequential ATRP results in polymer chains possessing benzoxazine groups, which could be further functionalized with other agents [ 20,21 ] or self-crosslinked. [12][13][14][15][16][17][18][19][20][21][22][23][24] RATH provides great convenience for preparation of functional initiators of atom transfer radical polymerization (bromination of benzoxazine compounds and PPO have been carried out with the RATH reaction using 1-(bromoethyl)benzene (BEB) as the alkylhalide reagents, CuBr as the catalyst, and 2,2′-bipyridyl as the ligand. Using bis(3-furfuryl-3,4-dihydro-2H-1,3-benzoxazinyl)isopropane (BPA-FBz) [ 25 ] as an example of RATH reagent, the solutions of all the chemicals in deuterated dimethylsulfoxide (DMSO-d 6 ) have been applied to 1 H NMR measurements to trace the RATH reaction between BPA-FBz and BEB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report has demonstrated a competitive pathway through phenoxy structures that nally convert to the phenolic polymers upon heating up to 160 C. 35 Furthermore, some special compounds, such as phenolic compounds, thiols, and chitosan ammonium, were used to react with benzoxazines 42,46,49,53,59,60 and a new mechanism, described as a ring-opening addition reaction mechanism (Scheme 1b), has been proposed. A recent report has demonstrated a competitive pathway through phenoxy structures that nally convert to the phenolic polymers upon heating up to 160 C. 35 Furthermore, some special compounds, such as phenolic compounds, thiols, and chitosan ammonium, were used to react with benzoxazines 42,46,49,53,59,60 and a new mechanism, described as a ring-opening addition reaction mechanism (Scheme 1b), has been proposed.…”
Section: The Proposed Reaction Mechanismmentioning
confidence: 99%
“…Another method is to incorporate reactive groups, such as amine, onto the Bz structures. But, only few studies have been reported until now due to relatively tedious preparation procedure [21,22].…”
mentioning
confidence: 99%